Developing and Validating the Career Personality Styles Inventory. (2nd January 2019) - Fu, Mingchen; Zhang, Li-Fang
ABSTRACT: The article describes the development and validation of the Career Personality Styles Inventory (CPSI). The CPSI comprehensively assesses Holland's career personality styles with only 22 items. Based on a series of 3 studies, we found satisfactory internal consistency, factor structure, and criterion validities of the newly constructed CPSI.